A single dual-targeting fluorescent probe enables exploration of the correlation between the plasma membrane and lysosomes. Issue 4 (5th January 2022) - Yu, Shimo; Wu, Shining; Zhang, Jing; Zhao, Xinfu; Liu, Xiaochan; Yi, Xibin; Li, Xuechen
Abstract : A dual-targeting probe was constructed to explore simultaneously label plasma membrane and lysosomes. With this probe, the correlation of the two organelles were investigated and the cholesterol (CL) contents in plasma membrane were spatially detected. Abstract : The interactions between organelles can maintain normal cell activity. Lysosomes, as waste disposal systems of cells, have many important interactions with the plasma membrane, especially in the repair of cracked plasma membrane. Unfortunately, a way to study the relationship between them synchronously is still lacking. Therefore, in this work, we constructed a dual-targeting probe (Mem-Lyso) to simultaneously visualize the plasma membrane and lysosomes for the first time. Taking advantage of dual-targeting, the probe Mem-Lyso could successfully track and analyze the dynamic changes of the plasma membrane and lysosomes in different bioprocesses. The experimental results demonstrated that, compared to the normal status, there was obvious fusion between the plasma membrane and lysosomes in the apoptosis process. Furthermore, because of the sensitivity to polarity, Mem-Lyso could label the plasma membrane and lysosomes with red and yellow colors in cells, respectively. Moreover, the skeleton and gastrointestinal wall of zebrafish were visualized by dual-color imaging, respectively. More importantly, the dual-targeting property endowed Mem-Lyso with the ability to spatially distinguish the cholesterol (CL) content in the plasma membrane, which provided a potential detection tool for biological research and diagnosis of related diseases.